Time management from Islamic Perspective: An exploratory study - Islam, Rafikul; Wahra, Ali Mohamed (2013)
Since time is limited in our life, we must utilize it in the best possible manner so that we can attain eternal success. Most of the existing guidelines on time management are developed by Western scholars some of which may not be consistent with the teachings of Islam. The main purpose of the present research is to develop some guidelines on time management from Islamic perspective. The findings from a quantitative survey are expected to provide some useful tips on time management from Islamic perspective. However, the study should be regarded as an exploratory one only.